Pemfigoid Bulosa: Faktor Risiko, Gejala Klinis, Diagnosis, dan Penatalaksanaan: Tinjauan Pustaka - Allatib, Arohid; Perdiyana, Angki; Dhamayanti, Marsita Endy (Cermin Dunia Kedokteran, 2026)
Bullous pemphigoid is an autoimmune disease characterized by subepidermal bullae, primarily affecting the elderly population. This disease involves autoantibodies targeting hemidesmosomal proteins, particularly BP180 and BP230, which play a crucial role in dermal-epidermal adhesion. Although bullous pemphigoid may resolve spontaneously, some cases exhibit a chronic course with significant complications. Diagnosis is based on history-taking, physical examination, and supportive investigations, including direct immunofluorescence (DIF) and enzyme-linked immunosorbent assay (ELISA) testing. Management involves topical corticosteroids for localized cases and systemic corticosteroids for more extensive involvement. Immunosuppressive agents such as methotrexate or azathioprine are used as adjunctive therapy. Several factors, including advanced age, neurological comorbidities, and exposure to certain medications, may increase the risk of developing bullous pemphigoid and influence its prognosis. Early recognition of characteristic clinical findings, confirmation through immunopathological examination, and selection of treatment according to disease severity and patient comorbidities are essential to improve clinical outcomes. Long-term monitoring is also required to detect relapse, treatment-related adverse effects, and complications associated with this disease. Although the mortality rate remains high, effective management can help alleviate symptoms and minimize long-term complications.